Design for safety and energy efficiency of the electrical onboard energy systems - Sfakianakis, Konstantinos; Vassalos, Dracos (2015 IEEE Electric Ship Technologies Symposium (ESTS), 2015)
Treating the ship as an autonomous floating vehicle, onboard energy systems have to be designed to ensure high reliability for the safety of the ship per se and, also, of the passengers and crew under all operating conditions and emergencies at minimum cost. To date, these objectives have been achieved by strict safety regulations, design simplicity and component redundancies in safety-critical systems at the design stage. However, designing the systems with the current measures, the cost-ineffectiveness of the former approach would suffer. In addition, lack of strict regulations concerning environmental impact and also the relatively low vessel operation costs, lead to energy savings not being considered as driving force in the shipping industry. The recently introduced IMO regulations came into force to address the above objectives, imposing specific requirements during ship design and operation. This paper introduces a novel methodology for improving onboard systems availability and energy efficiency by logical and numerical modelling of the shipboard electrical energy systems during design and operation through the combined assessment of electrical power systems availability and quantitative performance. These, i.e. availability and performance, linked to initial and operating costs allow for multi-objective design optimisation of the electrical power systems.